Factors influencing ion energy distributions in pulsed inductively coupled argon plasmas - Chen, Zhiying; Longo, Roberto C; Hummel, Michael; Carruth, Megan; Blakeney, Joel; Ventzek, Peter; Ranjan, Alok (Journal of physics. D, Applied physics, 2020)
Pulsed plasmas are important for the fabrication of nanoscale features. Source biasing is generally associated with the control of the ion to radical flux ratio; how the ion energy distribution function varies over a pulse period is also important. In this paper, we experimentally investigate the effect of pulse transients (i.e. power on to power off phases) on ion energy distributions during different RF source power duty cycles (99%-20%) in a compact inductively coupled argon plasma with time average RF power of 150 W at a frequency of 13.56 MHz and pressure of 20 mT (2.67 Pa). The ion energy distributions were measured by retarding field energy analyzer. With the decrease of RF power duty cycle, the increase of ion energy and energy spread is observed and ion energy distribution changes from single peaked to bi-modal. The effect of RF power duty cycle on the ion energy transition is discussed. Fluid and test particle simulations are used to illustrate the origin of features in the measured ion energy distributions. Capacitive coupling from the RF induction coils is highlighted as the origin for important features in the ion energy distributions.